Лозинское поле: роман / Григорий Медведев - Медведев Григорий Сергеевич (Земля родная, 1973)
Экземпляры: ф. 1 (20221013) / Инвентарный номер: 118700 / Цена: 10.00 / Авт.знак: М 42 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)